2015
DOI: 10.3892/ol.2015.3691
|View full text |Cite
|
Sign up to set email alerts
|

Positive fibroblast growth factor receptor 3 immunoreactivity is associated with low-grade non-invasive urothelial bladder cancer

Abstract: In addition to conventional clinicopathological parameters, molecular markers are also required in order to predict the course of disease in patients with urothelial bladder cancer (BC). Little is known about fibroblast growth factor receptor 3 (FGFR3) immunoreactivity and the clinical significance it may possess with regard to BC. The present study aimed to investigate the immunoreactivity of FGFR3 in primary urothelial bladder tumours, with regard to clinicopathological features and FGFR3 mutation status. Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…mRNA overexpression but not mutations or protein expression were also associated with favorable prognosis. In the literature, immunohistochemical data show protein overexpression also related to good prognosis 18 . In our series, there was a good correlation between mRNA expression and DNA mutation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA overexpression but not mutations or protein expression were also associated with favorable prognosis. In the literature, immunohistochemical data show protein overexpression also related to good prognosis 18 . In our series, there was a good correlation between mRNA expression and DNA mutation.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, EGFR seemed a prognostic factor for RFS and OS. In the TCGA data, a subgroup of tissue representing poor prognosis, called "basal-like", showed abnormal expression of the EGFR pathway 18,26 .The study by Rebouissou et al suggests that this well-selected group would be a good candidate for anti-EGFR treatment, provided that patients do not have mutations in the RAS pathway that would limit the response to treatment 27 . More recently, anti-EGFR targeted therapies have been evaluated in urothelial carcinomas in a trial demonstrating the benefit of cetuximab combined with paclitaxel as second-line treatment for metastatic bladder cancer 28 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that FGFR3 mutations occur in myeloma, cervix and bladder cancer ( 35 , 36 ), and is the most frequently mutated oncogene in NMIBC, primarily occurring in exons 7, 10 and 15 ( 37 ). Further studies have elucidate the FGFR3 overexpression and mutations are correlated ( 8 , 9 ). It has been demonstrated that FGFR3 is highly expressed in patients with recurrent metastatic bladder cancer ( 11 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that FGFR3 mutations are correlated with FGFR3 overexpression ( 8 ). Further study has revealed that 74% of patients with bladder cancer exhibiting a high expression of FGFR3 also possessed an FGFR3 mutation, indicating that FGFR3 expression is strongly associated with FGFR3 mutation ( 9 ). Clinically, chemoresistance occurs frequently in patients with bladder cancer that exhibit an aberrant activation of FGFR3.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies are needed to confirm this association. In addition, the FGFR3 protein expression level and FGFR3 mutation status were found to be significantly associated[31][32], but 15–26% of FGFR3 mutant tumors showed low levels of FGFR3 expression by IHC. In the present study, 12% of FGFR3 mutant tumors showed a low level of FGFR3 protein staining (S1 Appendix).…”
Section: Discussionmentioning
confidence: 99%